Hubungan antara Kemiskinan dan Pendidikan di Indonesia dengan Pertumbuhan Ekonomi - Ali Hardana (Penerbit Goodwood, 2023)
Purpose: The goal of this study is to determine the extent to which poverty and education affect economic growth in Indonesia. This analysis will serve as the foundation for formulating policies that will help Indonesia's economy expand. Methodology/approach: The type of research used is quantitative research. This study was taken from secondary data sources through the BPS website from 2012 to 2021. Although the multiple linear regression method of analysis was employed in this study. Multiple regression analysis was used to estimate the data, and the results show that while the poverty variable has no significant impact on Indonesia's economic growth and the education and poverty variables taken together have no impact either. Results/findings: The results of this study show that Education has a positive effect to growth variables economics. Poverty has a positive effect to economic growth. And Education and poverty in together has no effect to economic growth.